2007
DOI: 10.1049/iet-ipr:20050311
|View full text |Cite
|
Sign up to set email alerts
|

Document binarisation using Kohonen SOM

Abstract: An integrated system for the binarisation of normal and degraded printed documents for the purpose of visualisation and recognition of text characters is proposed. In degraded documents, where considerable background noise or variation in contrast and illumination exists, there are many pixels that cannot be easily classified as foreground or background pixels. For this reason, it is necessary to perform document binarisation by combining and taking into account the results of a set of binarisation techniques,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although many binarization techniques have been successfully applied to the MediaTeam Oulu Document Database [15], such techniques have difficulty in eliminating background noise on palm leaf manuscripts. Most of the reported work has been carried out on standard images that are not as complex and in poor quality as the ancient palm leaf manuscripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many binarization techniques have been successfully applied to the MediaTeam Oulu Document Database [15], such techniques have difficulty in eliminating background noise on palm leaf manuscripts. Most of the reported work has been carried out on standard images that are not as complex and in poor quality as the ancient palm leaf manuscripts.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria may be computed by machine or may be decided by visual human. Within this domain, Badekas and Papamarkos [15], applied some binarization techniques with a standard database (Mediateam Oulu Document) [16]. However, these documents are not as complex as palm leaf manuscripts.…”
Section: Introductionmentioning
confidence: 99%
“…The self-organizing map (SOM) [5,9] is widely applied approach for clustering and pattern recognition that can be used in many stages of the image processing, e. g. in color image segmentation [18], generation of a global ordering of spectral vectors [26], image compression [25], binarisation document [4] etc.…”
Section: Self-organizing Map In Edge Detection Performancementioning
confidence: 99%
“…Burgoyne et al (2007) studied binarisation algorithms of greyscale images in optical music recognition by pre-processing that differ significantly from non-music documents; their images are a special sub-case not included in our work. Badekas et al (2007) suggested a system for the binarization of normal and degraded documents for visualisation and recognition of text characters by a Kohonen adaptive neural network (Badekas and Papamarkos, 2007b); this is a realistic advance in real time character recognition. Badekas et al (2007) presented a technique for the binarization of text blocks in colour document images that contain text and graphics highly mixed with the background, based on a colour reduction; this is a common case in Byzantine text images and in our work.…”
Section: Binarization and Thresholdingmentioning
confidence: 99%